Working in partnership and building relationships as a specialist information service (Journal of EAHIL, 2018)
Deena Maggs, Head of Information and Knowledge Services at The King’s Fund, discusses the development, challenges and advantages of creating income generation activities and demonstrating impact. Key to success has been developing and maintain partnerships and reaching new audiences.